Clinical utility of the GAD-7 for detecting generalized anxiety in Quechua indigenous people - Caldichoury, Nicole; Quispe-Ayala, César; Coronado, Juan-Carlos; Castellanos-Alvarenga, Luis Mario; Salazar, David; Morales-Asencio, Breiner; Ripoll-Córdoba, Daniela; Quincho-Apumayta, Raúl; Cárdenas-Valverde, Juan; Camargo, Loida; Alcos-Flores, Karen; Layme-Condori, Eloy; et al. (Frontiers in Psychiatry, 2025)
The detection of Generalized Anxiety Disorder (GAD) in indigenous populations poses a challenge due to their holistic approach to health, which significantly contrasts with the Western biomedical model. Moreover, conventional assessment tools often overlook cultural particularities, compromising their effectiveness in these contexts.ObjectiveTherefore, this study aimed to analyze the diagnostic accuracy of the GAD-7 in the Quechua indigenous population of the Peruvian Andes.MethodTo address this issue, we conducted a case-control study to evaluate the clinical accuracy of the Generalized Anxiety Disorder Test (GAD-7) in rural Quechua communities of the Peruvian Andes. We included 147 GAD patients and 322 controls. The study involved four stages: cultural adaptation of the GAD-7, door-to-door evaluation, blind psychiatric and neuropsychological assessments, and application of the Quechua GAD-7. The adaptation used the Delphi method, focus groups, and bilingual judges. Factor analyses, reliability assessments, and diagnostic utility evaluations were performed.ResultsThe Quechua GAD-7 showed high content validity (Aiken’s V > 0.85), strong internal consistency (α = 0.912, ω = 0.85), and an area under the curve of 0.93. With a cutoff score of 11, it achieved 91.3% sensitivity and 86.1% specificity.ConclusionsThis is the first study to validate a Western test for GAD in indigenous populations.